Exploring nurses' role in guiding residents' workplace learning: A mixed‐method study. Issue 5 (26th October 2022) - Jansen, Iris; Silkens, Milou E. W. M.; Galema, Gerbrich; Vermeulen, Hester; Geerlings, Suzanne E.; Lombarts, Kiki M. J. M. H.; Stalmeijer, Renée E.
Abstract: Introduction: Understanding residents' workplace learning could be optimized by not only considering attending physicians' role but also the role of nurses. While previous studies described nurses' role during discrete activities (e.g. feedback), a more profound understanding of how nurses contribute to residents' learning remains warranted. Therefore, we used the educational concept of guidance and explored the extent to which residents' and nurses' perceptions align regarding nurses' guiding role and which reasons they provide for their perceptions. Methods: This mixed‐method study was conducted at four Dutch university medical centres in 2021. We simultaneously collected quantitative and qualitative data from 103 residents and 401 nurses through a theory‐informed questionnaire with a Likert‐scale and open‐ended questions. We analyzed quantitative data to explore respondents' perceptions of nurses' guiding role by using anova . The thematically analyzed qualitative open comments explored respondents' reasons for their perceptions. Results: Nurses indicated to provide significantly more support (p = .01) and guidance on learning from patient care (p < .01) than perceived by residents. Moreover, nurses indicated that attending physicians did not always involve them in guiding residents, whereas residents perceived nurses were being involved (p < .001). Themes suggest that nurses and residents could be divided into two groups: (i) respondents who felt that guiding was inextricably linked to good interprofessional collaboration and patient care and (ii) respondents who saw the guiding role as limited and emphasised the distinct fields of expertise between nurses and physicians. Conclusions: Residents and nurses felt that nurses played an important role in guiding residents' workplace learning. However, some residents did not always perceive to be guided. To further capitalise on nurses' guiding role, we suggest that residents can be encouraged to engage in the learning opportunities nurses provide to achieve optimal team‐based patient care. Abstract : In this study the authors demonstrate that residents and nurses believe nurses to have a role in guiding residents' workplace learning; perceptions of whether residents were being guided by nurses, however, differed.